2019
DOI: 10.1108/itp-10-2017-0360
|View full text |Cite
|
Sign up to set email alerts
|

Driving the internet and e-business technologies to generate a competitive advantage in emerging markets

Abstract: Purpose The purpose of this paper is to develop and empirically examine a comprehensive model that attempts to identify the factors that explain competitive advantage of implementing electronic business (e-business) in an emerging market. It seeks to fulfill an inevitable lack of conducting rigorous and intensive empirical studies on the Middle East and North Africa (MENA) region in which the internet use and e-business applications are on the rise. Design/methodology/approach This research is descriptive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 136 publications
2
19
0
2
Order By: Relevance
“…This comprises converting resources into value and extracting profits. Businesses need to manage customer needs, produce what customers demand, and to provide product value to customers (to manage Internet commerce) 19 .…”
Section: The Meaning Of E-commercementioning
confidence: 99%
“…This comprises converting resources into value and extracting profits. Businesses need to manage customer needs, produce what customers demand, and to provide product value to customers (to manage Internet commerce) 19 .…”
Section: The Meaning Of E-commercementioning
confidence: 99%
“…The literature argues that t's essential to examine the moderating effects of organizational variables such as technical capability on the relationship between IT adoption and competitive advantage (Chen, 2019). Investigating such a moderating role of technical capability (technology adoption barriers) in the relationship between IT adoption and competitive advantage can better explain technology adoption and its merit to create distinctive competitive advantage (Shehata & Montash, 2019;Chiu and Yang, 2019). Technical capability is defined as "the physical assets that are essential to adopt innovations, such as computer hardware, data, and networking" (Chen, 2019, p. 60).…”
Section: Technical Capability In the High Technology Industry Contextmentioning
confidence: 99%
“…Past studies have empirically confirmed that environmental context moderates the relationship between TOE factors and IT adoption. However, little is known about the moderating role of organizational-level factors such as technical capability in the relationship between IT adoption and competitive advantage (Chen, 2019;Shehata & Montash, 2019). strong technical capability can influence firms' competitive advantage, improve the overall quality of employees, enhance internal and external communication efficiency, facilitate the delivery of technical solutions for integrating advanced technologies, and then achieve firms' objectives (Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICT facilitates abroad range of organization's activities related to production, marketing, customer loyalty and employee performance (Reichstein, 2019). Shehata & Montash (2019) claim that ICT transformed the nature of products, markets, companies and the competition itself. ICT restructures many industries, enhance managing cost and created entirely new business models.…”
Section: Information and Communication Technology And Employee Performancementioning
confidence: 99%